Parental Support, Career Exploration, and Career Decision-Making Self-Efficacy in Junior High School Students - Annisa Maulidya Chasanah; Rose Mini Agoes Salim (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
The implementation of Curriculum 2013 brought changes to students' admissions to high school/vocational level. Students are required to choose their course earlier, with or without trial time, which marks the importance of career planning and efficacy to decide their future career for students since junior-high. This study examined the role of career exploration behavior (CEB) as a mediator between career-related parental support (CRPS) and career decision-making self-efficacy (CDSE). Data were obtained from 140 junior-high school students on grade VIII and IX in the 2018/2019 school year in the year of 2018/2019. The regression analysis showed that CRPS has significantly influenced relations with CDSE, with CEB only has a small role in partially mediating their relationship (b = .44, t(137) = 6.31, p = .000; coefficient = .22, SE = 3.91%, CI = .14 - .29). The result is fit with the social cognitive career theory (SCCT). Other results obtained from the additional analysis, instrumental assistance (b = .20, t(134) = 3.1, p = .041), and verbal encouragement (b = .16, t(134) = 2.06, p = .041) were able to influence the CDSE directly, but emotional support indirectly (coefficient = .09, SE = 3.29%, CI = .03 - .16) influences CDSE through CEB as mediator. These results may be affected by Indonesian's collectivist culture, which able to play a role in adolescents' development and their capacity to make their career-choice independently.